2008
DOI: 10.1002/aur.7
|View full text |Cite
|
Sign up to set email alerts
|

Face and object processing in autism spectrum disorders

Abstract: The nature and extent of face-processing impairments in individuals with autism spectrum disorder (ASD) remain contentious. The aim of this research study is to assess the face-and object-processing performance of individuals with ASD compared with typically developing controls. Our hypothesis was that individuals with ASD would be significantly impaired on tests of face processing but show intact object processing. More specifically, we tested two competing hypotheses to explain face-processing deficits: holi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 52 publications
(74 reference statements)
5
54
1
4
Order By: Relevance
“…Difficulties in perceiving and discriminating faces have been well documented in individuals with ASD (e.g., see Dawson, Webb, & McPartland, 2005, for review). Children and adults with ASD show poorer performance on a variety of face processing tasks compared with non-autistic individuals, including face recognition (Boucher, Lewis, & Collis, 1998;Ewing, Pellicano, & Rhodes, 2011a), face discrimination (Ewing et al, 2011a;Wallace, Coleman, & Bailey, 2008a), expression recognition (Rump, Giovannelli, Minshew, & Strauss, 2009;Wallace, Coleman, & Bailey, 2008b), and eye-gaze perception (Wallace, Coleman, Pascalis, & Bailey, 2006). Even when their performance is similar to that of non-autistic individuals, individuals with ASD appear to use atypical strategies, such as paying more attention to the mouth than the eyes (Klin, Jones, Schultz, Volkmar, & Cohen, 2002;Neumann, Spezio, Piven, & Adolphs, 2006;although see Falck-Ytter & von Hofsten, 2011, for a critique), and applying a local rather than holistic processing style (Joseph & Tanaka, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in perceiving and discriminating faces have been well documented in individuals with ASD (e.g., see Dawson, Webb, & McPartland, 2005, for review). Children and adults with ASD show poorer performance on a variety of face processing tasks compared with non-autistic individuals, including face recognition (Boucher, Lewis, & Collis, 1998;Ewing, Pellicano, & Rhodes, 2011a), face discrimination (Ewing et al, 2011a;Wallace, Coleman, & Bailey, 2008a), expression recognition (Rump, Giovannelli, Minshew, & Strauss, 2009;Wallace, Coleman, & Bailey, 2008b), and eye-gaze perception (Wallace, Coleman, Pascalis, & Bailey, 2006). Even when their performance is similar to that of non-autistic individuals, individuals with ASD appear to use atypical strategies, such as paying more attention to the mouth than the eyes (Klin, Jones, Schultz, Volkmar, & Cohen, 2002;Neumann, Spezio, Piven, & Adolphs, 2006;although see Falck-Ytter & von Hofsten, 2011, for a critique), and applying a local rather than holistic processing style (Joseph & Tanaka, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The study found evidence of atypicalities in children with ASD, since the children seemed to rely more on local facial elements than did typically developing children (Deruelle, et al, 2008). Similar conclusions were reached by Wallace, Coleman and Bailey (2008). In their study, holistic processing and second-order configural processing were investigated.…”
Section: Face Processing In Asdmentioning
confidence: 68%
“…Holistic processing was tested by asking participants to match different faces (or cars), while configural processing was assessed by asking participants to match faces (or houses) that differed either in configurations only or in features only. Wallace et al (2008) found an impairment in both aspects of face processing (holistic and configural) but intact object processing. Therefore, it was suggested that the consistently poor performance shown by ASD individuals represented a comprehensive cognitive impairment in face processing.…”
Section: Face Processing In Asdmentioning
confidence: 91%
See 1 more Smart Citation
“…Relative to typically developing individuals, differences and difficulties have been reported in processing of emotional expressions (see Harms, Martin, & Wallace, 2010) and social cues such as eye gaze (Nation & Penny, 2008; Senju & Johnson, 2009) (note—here and elsewhere we make use of preferred, identity-first terminology; Kenny et al, 2015). Atypicalities are also reported in the discrimination and recognition of face identity (Behrmann et al, 2006; Boucher, Lewis, & Collis, 1998; Croydon, Pimperton, Ewing, Duchaine, & Pellicano, 2014; Gepner, de Gelder, & de Schonen, 1996; Hauck, Fein, Maltby, Waterhouse, & Feinstein, 1998; Klin et al, 1999; Tantam, Monaghan, Nicholson, & Stirling, 1989; Wallace, Coleman, & Bailey, 2008), particularly when tasks involve a memory component or careful processing of the eyes (see, Weigelt, Koldewyn, & Kanwisher, 2012). These identity-processing difficulties are rarely as functionally debilitating as those deficits observed in “face blind” individuals with prosopagnosia (Behrmann & Avidan 2005; Yardley, McDermott, Pisarski, Duchaine, & Nakayama, 2008) but may nevertheless importantly contribute to the social communication and interaction difficulties characteristic of autism (Weigelt et al, 2012).…”
mentioning
confidence: 92%